Illocutionary Speech Acts on Stickers as Promotional Media of Mangroves Ecotourism in Bangkalan, Madura - Zulkhaeriyah, Zulkhaeriyah Zulkhaeriyah; Romadlani, M. Masqotul Imam; Rahayu, Lustya Suci; Zuhra, Siti Fatimatuz (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2024)
The primary goal of this research is to find the lingual forms and meanings of the language in vehicle stickers used as promotional media to increase ecotourism possibilities throughout the Mangroves Ecotourism area of Bangkalan by means of illocutionary speech acts. In this research, the descriptive and qualitative research methods were used. The data for this research came from a form of vehicle sticker that was first investigated to promote Mangrove Ecotourism in Bangkalan, Madura. The following Mangrove Ecotourism sites were included in this research: Labuhan Mangrove Education Park Bangkalan, Mangrove Martajasah, and Mangrove Tajungan, Kamal. The research carried out adopted George Yule's pragmatic theory and J.R Searle's illocutionary speech act as the theoretical framework, which provides a good explanation of the representative speech act, directive speech act, expressive speech act, commissive speech act, and declarative speech act. Then, concluded that directive speech act plays a major form of this research’s finding and discussion and representative speech act as the second form whose type is commonly used in the sticker as promotional media.